The Kos–Nisyros–Yali volcanic field - Bachmann, Olivier (2020)
The Kos–Nisyros–Yali volcanic field has produced a range of volcanic products over the last 3 million years. Volumetrically, silicic magma dominates, and activity includes one of the largest known explosive eruptions of the Aegean arc, the >60 km3 (dense-rock equivalent), 161 ka rhyolitic Kos Plateau Tuff. The Kos–Nisyros–Yali volcanic field is situated within an area of active crustal extension, which has greatly influenced magmatic processes and landscape development in the region. Recent seismic unrest, surface deformation and intense geothermal activity indicate that the system remains active, particularly around the Nisyros and Yali edifices. These signs of magmatic activity, together with the fact that the most recent eruptions have become increasingly silicic, would justify detailed monitoring of the area.